Effect of clavulanic acid on the activity of ticarcillin against Pseudomonas aeruginosa. - Tausk, F (1986)
We studied the ability of clavulanic acid (CA) to induce beta-lactamase in Pseudomonas aeruginosa isolates and what effect this might have on the susceptibilities to beta-lactam agents. We first used a disk approximation method to test 4 laboratory and 16 clinical P. aeruginosa isolates against antipseudomonal beta-lactam agents for truncation by CA and found this to be very common. All antimicrobial compounds except imipenem demonstrated truncation in the vicinity of CA. We also evaluated the extent to which chromosomal beta-lactamase is induced by CA and found this to occur to some degree in most isolates and to be dependent on the concentration of CA. Finally, we performed time kill curves on these isolates to compare bacterial growth in ticarcillin alone with growth in ticarcillin-CA (the CA at 2 or 4 micrograms/ml). We found that CA at this concentration has neither an antagonistic nor a synergistic antibacterial effect in combination with ticarcillin.